1987
DOI: 10.1038/327426a0
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQ is epistatic to HLA-DR in controlling the immune response to schistosomal antigen in humans

Abstract: Antigens that produce an antibody response in some members of a species may fail to do so in others. The response to an antigen is controlled by a gene termed the immune response (Ir) gene, which is transmitted as a single dominant trait. We have provided evidence for similar immune suppression (Is) genes which control non-responsiveness through the antigen specific suppressor T cell. The non-responsiveness is also dominantly inherited and the Is genes are linked to the histocompatibility (HLA) antigen system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(83 citation statements)
references
References 0 publications
3
78
0
2
Order By: Relevance
“…It is interesting to note that monoclonal antibody directed against HLA-DQ also restored the immune response to Sj in vitro in nonresponders with HLA-DR2-DQw6-Dwl2 haplotype (Hirayama et al, 1987) (Fig. 4).…”
Section: Evidence For the Active Suppression And Epistatic Interactiomentioning
confidence: 89%
See 1 more Smart Citation
“…It is interesting to note that monoclonal antibody directed against HLA-DQ also restored the immune response to Sj in vitro in nonresponders with HLA-DR2-DQw6-Dwl2 haplotype (Hirayama et al, 1987) (Fig. 4).…”
Section: Evidence For the Active Suppression And Epistatic Interactiomentioning
confidence: 89%
“…Actually there is no doubt that HLA-DR molecules are acting as the products of HLA-linked Ir-genes, because (1) HLA-DR molecules are the restriction elements in the interaction between CD4+ helper T cells and antigen presenting cells in the response to many antigens such as streptococcal cell wall antigen (SCW) Sone et aI., 1985;Hirayama et al, 1986), schistosomal antigen (Sj) (Hirayama et aL, 1987), Myeobacterium leprae antigen (ML) (Kikuchi et al, 1986) and so on, and (2) anti-HLA-DR monoclonal antibodies completely abolish the immune response to those antigens Sone et al, 1985;Hirayama et al, 1986;Kikuchi et al, 1986;Hirayama et al, 1987). However, genetic analysis of the immune response to those antigens in families or populations revealed that responsiveness is recessive and nonresponsiveness to those antigens is a dominant genetic trait which is tightly linked to HLA (Sasazuki et aI., 1980a;Sasazuki et al, 1983;Watanabe et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…However, their expression on antigen-presenting cells can be induced by interferon 7 [14], and infectious agents such as the Epstein-Barr virus [15]. It has been postulated that DQ molecules exercise epistatic action over DR molecules [16] and that they are the mediators of immunosuppression [17].…”
mentioning
confidence: 99%
“…The HLA plays an important role in controlling the immune system and is known to be associated with various diseases such as auto-immune diseases (Todd et al, 1988;Sasazuki et al, 1983), infectious diseases (Hirayama et al, 1987;Nishimura and Sasazuki, 1987) and virus-associated tumors (Burt et al, 1994).…”
Section: Discussionmentioning
confidence: 99%